Assessment of rainfall distribution over peninsular Malaysia using satellite-based rainfall data - Noor Ain , Mohd Nasir@Mazlan (2015)
Rainfall distribution is spatial and temporal variability. High spatial and temporal resolution data are required for studying the rainfall distribution over Peninsular Malaysia. The availability of accurate rainfall data at proper temporal and spatial scale is vital for water resources sustainable planning and security. Thus, satellite-based is an alternative source of information especially for developing country like Malaysia where there are many areas that do not have ground observation. The main objective of this study was to assess rainfall distribution over Peninsular Malaysia using satellite-based rainfall. The specific objectives as follows; To produce monthly average rainfall satellitebased map; and To analyze the rainfall distribution statistically. Data is collected from TRIMIrVI Multi-satellite Precipitation Analysis (TMPA) version 7 based images as monthly rainfall from public domain for 5 years period of time (July 2009-June 2014). Rainfall data from the satellite were processed and converted into Geographical Information System (GIS) ready to produce map. Monthly rainfall distribution is statistically analysed and assessed. For study period, July 2009-June 2014, the average of annual rainfall distribution from TMPA satellite- based calibrated image is 2376 mm, 4.6% more than previous report. The annual rainfall distribution for 5 years period time of July 2009-June 2010, July 2010-June 2011, July 2011-June 2012, July 2012-June 2013 and July 2013June 2014 are 2490 mm(equal previous report), 2439 mm (<2%),2532 mm (>17 1/6), 2372 mm (<5%) and 2048 mm (<18%), respectively.Error! Bookmark not defined.